Lung cinescintigraphy in the dynamic assessment of ventilation and mucociliary clearance of asbestos cement workers. Issue 9 (September 1996) - Di Lorenzo, L; Mele, M; Pegorari, M M; Fratello, A; Zocchetti, C; Capozzi, D
Abstract : OBJECTIVES: To verify in vivo whether lung cinescintigraphy confirms the effect of asbestos on the patency of the smallest airways and on the efficiency of mucociliary clearance in asbestos cement workers. METHODS: 39 male subjects were examined: 30 asbestos cement workers and nine workers never exposed to occupational respiratory irritants. All subjects had a chest radiograph (International Labour Organisation (ILO) 1980); standard questionnaire on chronic bronchitis; spirometry; arterial blood gas analysis; carbon monoxide transfer factor (TLcosb); pulmonary O2 and CO2 ductances (DuO2, DuCO2); electrocardiogram; and lung cinescintigraphy after radioaerosol inhalation for the measurement of mucociliary clearance time in vivo in the smallest ciliated airways and for the assessment of radioaerosol deposition in alveoli (alveolar deposition index). RESULTS: Apart from nine non-exposed subjects, the 30 asbestos cement workers were so classified on the basis of chest radiography: nine of them as healthy exposed, 10 with pleural plaques, and 11 with asbestosis. The four groups had similar ages, work seniority, and smoking habits. Exercise dyspnoea was significantly more frequent in asbestos cement workers. Lung function variables of workers with effects related to asbestos were significantly lower than the other two groups. The PaO2, TLcOsb and DuO2 mean values were significantly lower in exposed workers than non-exposed. The mean PacO2 value was significantly higher in the asbestosis group than in the other three groups. Workers with effects related to asbestos showed a significantly lower alveolar deposition index and a significantly higher mucociliary clearance time than the other two groups. Subjects with asbestosis showed similar differences from those with pleural plaques. CONCLUSIONS: Lung cinescintigraphy confirms in vivo the effects of asbestos on bronchiolar and alveolar patency and on efficiency of mucociliary clearance in the smallest ciliated airways. Finally, lung cinescintigraphic variables are able to discriminate workers with asbestosis from those with pleural plaques.